Strumentale o sostanziale? Il web 2.0 dei partiti politici e della società civile - Putini, Antonio (SocietàMutamentoPolitica, 2017)
This article aims to depict an overview about web-sites participative structure of the main political and civil collective actors in Italy. Which kind of tools appear in the Italian parties web-sites? And, above all, which kind of participative possibilities they allow to users?